Ascorbic Acid and Polyphenols Mediated Green Synthesis of Silver Nanoparticles from Tagetes erecta L. Aqueous Leaf Extract and Studied Their Antioxidant Properties. (3rd August 2021) - Tyagi, Pankaj Kumar; Tyagi, Shruti; Gola, Deepak; Arya, Arvind; Ayatollahi, Seyed Abdulmajid; Alshehri, Mohammed M.; Sharifi-Rad, Javad
Abstract : Silver nanoparticle synthesis of the leaf extract Tagetes erecta L . enriched with ascorbic acid and polyphenols has been investigated. The color of the golden yellow extract has changed to pinkish-brown due to the reduction of Ag + to the colloidal solution of AgNPs and a sharp absorption peak at 420 nm under the UV-Vis spectrophotometer. In addition, the Fourier Transfer Infrared Spectroscopy (FTIR) estimation was completed in order to recognize and identify the biomolecules present in the extract acting as a reducing and capping agent for the AgNPs. The X-ray diffraction (XRD) peaks at (111), (201), (220), and (311) confirm the presence of monoclinic crystals in the solution. The morphology and size of the particles were provided by transmission electron microscopy (TEM) images of AgNPs. At a scale of 100 nm, synthesized AgNPs were predominantly spherical with a size range of 7-35 nm. In comparison to 7.39 mg/100 g in AgNPs, aqueous leaf extract was 55.14 mg/100 g higher in ascorbic acid. The phenolic and flavonoid content of extract was 52.54 ± 2.15  mg (GAE/100 g) and 15.43 ± 0.34  mg (QE/mL), and the colloidal AgNP solution was 21.45 ± 1.15  mg (GAE/100 g) and 8.05 ± 2.42  mg (QE/mL), respectively. Phenolic and flavonoid contents play a major role as a reducing agent and reduce the precursor AgNO3 into AgNPs. The DPPH scavenging assay also assessed the antioxidant properties of extract and its derived AgNPs. As compared antioxidant value to aqueous leaf extract (mg/mL), higher percentage inhibition (PI) was found in AgNPs and free-radical scavenging activity of extract and AgNPs were directly linked to their concentrations. Results of this research have discovered a higher potential for free-radical scavenging AgNPs and will help to develop new and more potent antioxidants for the treatment of different diseases caused by oxidative stress; the higher antioxidant properties bearing AgNPs might be used.